Effects of NAA and BAP, Double-Layered Media, and Light Distance on In Vitro Regeneration of Nelumbo nucifera Gaertn. (Lotus), an Aquatic Edible Plant - Hashimah, Elias; Noraini, Mahmad; Rosna, Mat Taha; Rashidi, Othman; Azani, Saleh; Nor Azlina, Hasbullah (Hindawi Publishing Corporation, 2014)
In vitro direct regeneration of Nelumbo nucifera Gaertn. was successfully achieved from immature explants (yellow plumule) cultured on a solid MS media supplemented with combinations of 0.5 mg/L BAP and 1.5 mg/L NAA which resulted in 16.00 ± 0.30 number of shoots per explant and exhibited a new characteristic of layered multiple shoots, while normal roots formed on the solid MS basal media. The double-layered media gave the highest number of shoots per explant with a ratio of 2 : 1 (liquid to solid) with a mean number of 16.67 ± 0.23 shoots per explant with the formation of primary and secondary roots from immature explants. In the study involving light distance, the tallest shoot (16.67 ± 0.23 mm) obtained from the immature explants was at a light distance of 200 mm from the source of inflorescent light (1000 lux). The plantlets were successfully acclimatized in clay loam soil after 8 months being maintained under in vitro conditions.